Environmental health risk assessment in opthalmic lens manufacturing - De Vera, Estrella M. (2008)
Records in an ophthalmic lens manufacturing facility located in Laguna show an average of three accidents annually for the past five years. Also, occupational illness such as cases of eye and skin irritation is also significantly high with 9.14 severity rate for the year 2007. Furthermore, clinic report indicates 17 cases of mild hearing loss for 2007 and one case of carpal tunnel syndrome (CTS) in quarter one of 2008. Thus, this study is significant to review and evaluate the hazards and environmental health risks associated in an ophthalmic lens manufacturing.